2006
DOI: 10.1093/aob/mcl010
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Vascular Systems in C3 and C4 Grasses: A Two-dimensional Analysis

Abstract: It seems that C(4) grasses have structurally a superior photosynthate translocation and water distribution system by developing denser networks of small longitudinal and transverse veins, while keeping a constant density of large longitudinal veins. The bambusoid and panicoid C(3) grasses have a vascular system that is more similar to that in C(4) grasses than to that in the festucoid C(3) grasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 58 publications
2
73
2
Order By: Relevance
“…This is surprising as previous studies have shown that the leaf vascular system of C4 plants supports a superior photosynthate translocation and distribution system relative to C3 plants (McKown and Dengler, 2009;Ueno et al, 2006). In comparison to other studies performed on different species, this MRT is shorter than those generally observed on trees (Hogberg et al, 2008;Ruehr et al, 2009;Warren et al, 2012) but more comparable to those observed on shorter vegetation such as grasses, shrubs and tundra vegetation Subke et al, 2012).…”
Section: Assimilation Of C Into Plant Biomasscontrasting
confidence: 70%
“…This is surprising as previous studies have shown that the leaf vascular system of C4 plants supports a superior photosynthate translocation and distribution system relative to C3 plants (McKown and Dengler, 2009;Ueno et al, 2006). In comparison to other studies performed on different species, this MRT is shorter than those generally observed on trees (Hogberg et al, 2008;Ruehr et al, 2009;Warren et al, 2012) but more comparable to those observed on shorter vegetation such as grasses, shrubs and tundra vegetation Subke et al, 2012).…”
Section: Assimilation Of C Into Plant Biomasscontrasting
confidence: 70%
“…The previous classification of plants as C 3 or C 4 species especially in the genus Cyperus has been based largely on any or a combination of the followings; stable carbon isotope ratio, CO 2 compensation point analyses (Bruhl and Wilson, 2007), leaf anatomical characteristics such as Kranz anatomy (Martins and Alves, 2009;Ayeni et al, 2015), interveinal distance (Ueno et al, 2006;Faniyan et al, 2013) and one cell distant criterion (Bruhl and Wilson, 2007;Faniyan et al, 2013;Ayeni et al, 2015). Out of all the species investigated in this study, only C. difformis and C. haspan have been previously reported to be C 3 species, the rest are C 4 species (Bruhl and Wilson, 2007;Martins and Alves, 2009) with the exception of C. dilatatus with yet to be identified photosynthetic pathway status.…”
Section: Discussionmentioning
confidence: 99%
“…The density of the large longitudinal leaf veins is similar in C 3 and C 4 grasses but C 4 grasses have denser transverse leaf veins and denser small longitudinal veins than C 3 grasses (Ueno et al 2006). As a result C 4 grasses have a photosynthate translocation and water distribution system which is structurally different from C 3 plants, and which is considered (e.g., Woerner & Martin 1999) to contribute to better water use efficiency than C 3 species.…”
Section: Properties Evolution and Distribution Of C 4 Grassesmentioning
confidence: 99%